The Cambridge companion to Newton - Cohen, I Bernard (Cambridge University Press, 2013)
Newton's philosophical analysis of space and time / Robert Disalle -- Newton's concepts of force and mass, with notes on the Laws of Motion / I. Bernard Cohen -- Curvature in Newton's dynamics / J. Bruce Brackenridge and Michael Nauenberg -- Methodology of the Principia / George E. Smith -- Newton's argument for universal gravitation / William Harper -- Newton and celestial mechanics / Curtis Wilson -- Newton's optics and atomism / Alan E. Shapiro -- Newton's metaphysics / Howard Stein -- Analysis and synthesis in Newton's mathematical work / Niccolò Guicciardini -- Newton, active powers, and the mechanical philosophy / Alan Gabbey -- Background to Newton's chymistry / William Newman -- Newton's alchemy / Karin Figala -- Newton on prophecy and the Apocalypse / Maurizio Mamiani -- Newton and eighteenth-century Christianity / Scott Mandelbrote -- Newton versus Leibniz : from geomentry to metaphysics / A. Rupert Hall -- Newton and the Leibniz-Clarke correspondence / Domenico Bertoloni Meli.